The third degree : the triple murder that shook Washington and changed American criminal justice. - Seligman, Scott D. (Potomac Books, an imprint of the University of Nebraska Press, 2018)
"'The Third Degree' is the true story of a young man's abuse by the Washington police and an arduous, seven-year journey through the legal system that drew in Warren G. Harding, William Howard Taft, Oliver Wendell Holmes, John W. Davis, and J. Edgar Hoover. The ordeal culminated in a sweeping Supreme Court ruling penned by Justice Louis Brandeis that set the stage for the Miranda warning many years later. Scott D. Seligman argues that the importance of the case hinges not on the defendant's guilt or innocence but on the imperative that a system that presumes one is innocent until proven guilty provides protections against coerced confessions."--Jacket